Profils Sociodemographique, Economique Et Alimentaire Chez Des Enfants Malnutris Aigus, Ages De 06 A 59 Mois, Reçus Au Centre Hospitalier Universitaire De Treichville (Abidjan-Cote D’ivoire) - K. J., Kouamé; K. E., Amoikon; K. G., Kouamé; S., Kati-Coulibaly (European Scientific Journal, ESJ, 2017)
In this descriptive and transversal work, the main objective is to establish the socio-demographic, economic and nutritional profiles of the children, aged between 06 and 59 months, acutely malnourished, consulted and / or hospitalized in pediatric emergency departments and Of the University Hospital of Treichville (UHT). This study is conducted on 290 children, aged between 06 and 59 months. A questioning anthropometric, socio-demographic, economic and food data allows the diagnosis of the nutritional status of each child and the descriptive statistical analysis of the patient. The results show that the prevalence of acute malnutrition is 55.86%, with 35.17 % cases of severe acute malnutrition and 20.68 % of cases of moderate acute malnutrition. The population of acute malnourished children in this study consisted of 84 girls and 78 boys, a sex ratio of 0.928. The children (133) victims of this type of malnutrition come, predominantly and significantly, from the precarious habitats. 126 have out-of-school mothers and 129 have consumed food of diversification or poor quality supplement. In 110 acute malnutrition, the daily family food budget is between 1500 FCFA and 3000 FCFA. At last, the index of food consumption score, also called food consumption, is referred to as a limit in 98. Finally, in this study, the risk factors having a significant impact on nutritional status are the precariousness of the habitat Place of residence), maternal education, complement food quality or diversification, food insecurity, age of complement and current diet.